Diurnal Intraocular Pressure Patterns are Not Repeatable in the Short Term in Healthy Individuals - Realini, Tony (2010)
PURPOSE: To evaluate the short-term repeatability of diurnal intraocular pressure (IOP) patterns in eyes of subjects without glaucoma. DESIGN: Observational cohort study. PARTICIPANTS: 40 healthy subjects without glaucoma. METHODS: Subjects underwent 12-hour diurnal IOP assessment sessions from 0800 to 2000 on two visits one week apart. IOP was assessed by Goldmann applanation tonometry. An analysis was performed to determine the strength of association of individual diurnal IOP patterns from the first visit to the second visit. The intraclass correlation coefficient (ICC) was utilized to analyze both agreement of IOP values at each time point between visits and IOP change over time periods between time points between visits. MAIN OUTCOME MEASURE: Diurnal IOP patterns. RESULTS: Between-visit agreement of IOP values at each time point was generally fair to good, with ICCs ranging from 0.37 to 0.62 in right eyes and from 0.35 to 0.71 in left eyes. Between-visit agreement of IOP change over time periods between time points was uniformly poor and often below that expected by chance alone, with ICCs ranging from −0.25 to 0.15 in right eyes and from −0.40 to 0.22 in left eyes. CONCLUSIONS: Eyes of healthy individuals do not manifest a sustained and reproducible diurnal IOP pattern when measured by Goldmann tonometry. A single-day assessment of IOP poorly characterizes the diurnal IOP pattern.